Low friction mechanism of chlorine-doped amorphous carbon films sliding against an aluminium alloy. (November 2017) - Tokuta, Yuuki; Itoh, Takashi; Shiozaki, Takahiko; Kawaguchi, Masahiro; Sasaki, Shinya
Abstract: The effect of chlorine-doping on the tribological properties of amorphous carbon films was investigated. Chlorine-doped amorphous carbon films were deposited using a plasma-based ion implantation and deposition (PBII&D) method with vaporized tetrachloroethylene as a precursor. During sliding tests with aluminium alloy counter parts, chlorine-doped amorphous carbon films showed lower friction coefficients compared to hydrogenated amorphous carbon films. Both aluminium and a chlorine-based hydrate were observed on the wear track of the carbon films. This hydrate was a tribofilm formed via a tribochemical reaction during sliding between the chlorine-doped amorphous carbon films and aluminium alloy. The viscosity of this tribofilm was similar to polyalpha olefin and we propose that it acted as a lubricant and lowered the friction coefficient. Highlights: Cl-doped a-C:H films deposited using plasma-based ion implantation and deposition. Cl-doped a-C:H films reduced the friction coefficient compared to non-doped a-C:H films. Aluminium chloride hydrate tribofilm formed during sliding tests. Tribofilm acted as lubricant via a viscosity similar to polyalpha olefin.